2018
DOI: 10.1371/journal.pone.0196478
|View full text |Cite
|
Sign up to set email alerts
|

Role of matrix metalloproteinases 2 and 9, toll-like receptor 4 and platelet-leukocyte aggregate formation in sepsis-associated thrombocytopenia

Abstract: BackgroundThe development of thrombocytopenia in sepsis is a poor prognostic indicator associated with a significantly increased mortality risk. Mechanisms underlying this phenomenon remain to be clearly elucidated. Matrix metalloproteinases (MMPs) are enzymes that regulate the turnover of the extra-cellular matrix. MMP-2 is recognised as a platelet agonist with MMP-9 proposed as an inhibitor of platelet activation. The existence of MMP-9 in platelets is a subject of debate. There is limited evidence thus far … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Leite et al [19] has found that low serum albumin was associated with higher mortality-every 1 g/dL increase in serum albumin at admission reduced the risk of death by 73% (OR: 0.27, 95%CI: 0.14-0.51: P<0.001). Similarly, many other studies have confirmed that albumin is closely related to the prognosis of neurological function [20,21]. Our study is consistent with the results mentioned above.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Leite et al [19] has found that low serum albumin was associated with higher mortality-every 1 g/dL increase in serum albumin at admission reduced the risk of death by 73% (OR: 0.27, 95%CI: 0.14-0.51: P<0.001). Similarly, many other studies have confirmed that albumin is closely related to the prognosis of neurological function [20,21]. Our study is consistent with the results mentioned above.…”
Section: Discussionsupporting
confidence: 94%
“…Akca et al [37] studied 1,440 patients admitted to the ICU and showed that 30% of patients had a reduced platelet count at admission (PLT<150×10 9 /L), and the survivors had higher platelet counts. During the inflammatory period before CPR, reduced production or increased depletion of platelets leads to thrombocytopenia, which can cause microvascular thrombosis and multiple organ dysfunction [21]. The dysregulated platelets interact with vascular endothelium, lead to leakage of inflammatory factors and further damage brain tissue [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, a more recent study showed that although there was a tendency toward higher levels of TLR4 expression in the platelets of septic and thrombocytopenic patients, this did not reach statistical significance compared with nonthrombocytopenic septic patients. Remarkably, whereas platelets from normal donors increased their TLR4 expression upon stimulation a similar effect was not observed in septic patients, probably due to the already higher levels of TLR4 . In addition, in a very small sample of patients ( n = 7), Claushuis et al.…”
Section: Relevance Of Platelet Tlr4 In the Clinicmentioning
confidence: 88%
“…Remarkably, whereas platelets from normal donors increased their TLR4 expression upon stimulation a similar effect was not observed in septic patients, probably due to the already higher levels of TLR4. 53 In addition, in a very small sample of patients (n = 7), Claushuis et al found that platelets from septic patients showed platelet activation but unaltered TLR4 expression. 23 Because pre-clinical studies have shown that platelet TLR4 and platelet activation are required for NET formation, 42 we studied the relationship between NETosis and platelet activation in septic and burned patients, that is, two acute inflammatory diseases, one infectious and the other sterile.…”
Section: Relevance Of Platelet Tlr4 In the Clinicmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) are reorganizing the extracellular matrix [48,49]. MMP9 is only present in humans, its low expression affects platelet activation [50] (Table S2 and [51]). Platelet expression differences in tissue inhibitors of metalloproteinase (TIMPs), such as TIMP1, TIMP2 and TIMP3 affect activities of MMPs and by this platelet aggregation [52,53].…”
Section: Speci C Differences In the Central Cascadementioning
confidence: 99%